2018
DOI: 10.1158/0008-5472.can-17-0576
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Quantifies Immune Cell Transcript Levels, Metastatic Progression, and Survival in Osteosarcoma

Abstract: Overall survival of patients with osteosarcoma (OS) has improved little in the past three decades and better models for study are needed. OS is common in large dog breeds and is genetically inducible in mice, making the disease ideal for comparative genomic analyses across species. Understanding the level of conservation of inter-tumor transcriptional variation across species and how it is associated with progression to metastasis will enable us to more efficiently develop effective strategies to manage OS and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 35 publications
(46 reference statements)
3
109
0
Order By: Relevance
“…nih.gov/geo/), and subsequently used to perform WGCNA and DEG analysis. The GSE87624 dataset, comprising 44 human patient OS samples and 3 normal bone samples, was first published by Scott et al (22).…”
Section: Methodsmentioning
confidence: 99%
“…nih.gov/geo/), and subsequently used to perform WGCNA and DEG analysis. The GSE87624 dataset, comprising 44 human patient OS samples and 3 normal bone samples, was first published by Scott et al (22).…”
Section: Methodsmentioning
confidence: 99%
“…Many are monospecific antibodies in which both binding sites are directed against the same target; others are bispecific antibodies where the binding sites are directed to different targets, allowing engagement of immune cells, inhibition of signalling pathways, or delivery of cytotoxic molecules . Studies have suggested a correlation between prognosis and the presence of tumour infiltrating lymphocytes as well as with specific patterns of infiltration within the tumour microenvironment . A better understanding of the sarcoma microenvironment of different sarcoma subtypes will be critical to the development of new therapeutic strategies focused on targeting and manipulating the microenvironment to overcome immune evasion .…”
Section: Immunotherapy Approaches For Canine Sarcomasmentioning
confidence: 99%
“…113,114 Studies have suggested a correlation between prognosis and the presence of tumour infiltrating lymphocytes as well as with specific patterns of infiltration within the tumour microenvironment. [115][116][117][118][119][120] A better understanding of the sarcoma microenvironment of different sarcoma subtypes will be critical to the development of new therapeutic strategies focused on targeting and manipulating the microenvironment to overcome immune evasion. 121 A plausible approach is to link mAbs to recombinant toxins to generate ligand-directed "immunotoxins," or to radioisotopes, to enable energy release from the radioisotope into a solid tumour to kill both tumour and surrounding stromal cells.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Approximately 20% of dogs will survive more than two years [9][10][11]. The prognosis for osteosarcoma is similarly poor: Unless early and intense treatment is started upon detection, the average survival time is 3 months without treatment [12][13][14]. Canines with malignant melanoma have a median survival time ranging from three to 18 months, depending on the stage at diagnosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most effective management of canine appendicular osteosarcoma involves the incorporation of multimodal therapy to address the primary tumor and metastatic disease [14,18]. Palliative and curative-intent treatments are used for the bilateral synchronous appendicular bone tumors [19].…”
Section: Introductionmentioning
confidence: 99%